Properties of Multi-Valued Functions - Charatonik, Włodzimierz; Michalik, Daria (Topology Proceedings, 2021)
For a given topological property P of mappings, we say that a multi-valued function f: X Y is dir-P(co-P) if the projection from the graph of f to Y (onto X ) has property P. In this article, we investigate properties of dir-P and co-P functions. We discuss composition property, composition factor property, and product property of such functions.